Chromium - VI reagents synthetic applications - Sundaram, S.; Raghavan, P. S. (SpringerBriefs in molecular science., 2011)
Chromic acid and chromium oxide are the two versatile Cr(VI) oxidants known to organic chemists for decades. The introduction of the Core's reagent , viz: pyridinium chlorochromate, in 1975 followed by the publications on several Cr(VI) oxidizing agents containing the -onium chromates and halochromates in the last three decades have very much changed the chemistry of oxidations with Chromium VI. Several of these new reagents have been shown to be mild so that they can be handled easily and the reacton products may also be controlled. Some of them are highly selective oxidants for positions like allylic hydroxylic group, etc., and some other are highly regioselective. The information on more than 36 such reagents reported in various internationally reputed journals spanning about 280 references have been collected and provided in this book in such a manner that it will be very useful for professionals, researchers, teachers and graduate students working in organic synthesis.